Challenges of Diagnosing Viral Myocarditis in Adolescents in the Era of COVID-19 and MIS-C. (4th October 2021) - Shah, Hemali P.; Frye, Richard; Chang, Sunny; Faherty, Erin; Steele, Jeremy; Karnik, Ruchika
Abstract : Myocarditis has a wide array of clinical presentations ranging from asymptomatic to sudden cardiac death. Pediatric myocarditis is a rare disease, with an estimated annual incidence of 1 to 2 per 100, 000 children though its true prevalence remains unknown due to its variable and often subclinical presentation. The diagnosis of myocarditis is challenging in the era of COVID-19 and Multisystem Inflammatory Syndrome in Children (MIS-C), which can have overlapping clinical conundrum. Here, we present a case of a 17-year-old male presenting with chest tightness, shortness of breath, and electrocardiogram (EKG) findings concerning for myocardial injury along with elevated inflammatory markers such as D-dimer, ESR (Erythrocyte Sedimentation Rate), and CRP (C-Reactive Protein). We discuss the key elements of our clinical experience with this case and review the literature for pediatric myocarditis, with a focus on differentiating it from MIS-C in the current COVID-19 pandemic era.